Impact of D2 vs D3 dissection in right sided colon cancer, on the mortality and morbidity of patient - Gani, Mubashir; Kaleem, Zahid; Wani, Aizul Khursheed; Parray, Fazl Qadir; Chowdri, Nisar Ahmad (International Surgery Journal, 2024)
Background: Colorectal cancer is the third most common type of cancer worldwide. It is more prevalent in elderly age group. Genetic and environmental factors play a role. Extent of lymph node dissection determines the prognosis and overall survival of the patient. Methods: This study was conducted in colorectal division of Department of General and minimal invasive surgery in SKIMS Soura from June 2020 to May 2023. It was a prospective study comprising of 55 patients. The patients were studied in two groups: D2 and D3, and were compared on the basis of age group, gender, comorbidities, post operative complications, lymph node yield, operative time and mean blood loss. Results: A total of 56 patients were divided into two groups; Group D2 (n=33) and Group D3 (n=23) with majority having above 70-year age in D2 and 50-59 years of age in D3. There was no predilection for any gender. Hypertension was the most common comorbidity in both the study groups. There were statistically insignificant differences between two groups in terms of post operative complications, mean operative time and mean operative blood loss. Majority of the patients in both the groups had Clavein Dindo Grade I 16 (48.5%) in D2 and 13 (56.5%) in D3. Mean lymph node yield in Group D2 was 14.3±2.27 and in Group D3 lymph node yield was 23.7±4.86. Conclusions: D3 dissection in colon cancer resulted in a significant higher lymph node yield. Although both the procedures have almost similar complication rate but D3 dissection is an oncologically superior procedure.